Cullin 3 Ubiquitin Ligases in Cancer Biology: Functions and Therapeutic Implications - Chen, Hsin-Yi; Chen, Ruey-Hwa (Frontiers in Oncology, 2016)
Cullin-RING ubiquitin ligases are the largest E3 ligase family in eukaryotes and are multi-protein complexes. In these complexes, the Cullin protein serves as a scaffold to connect two functional modules of the ligases, the catalytic subunit and substrate-binding subunit. To date, eight members of the Cullin family proteins have been identified. In the Cul3 ubiquitin ligases, BTB domain-containing proteins function as a bridge to connect Cul3 and substrates. While the BTB domain is responsible for Cul3 binding, these proteins usually contain an additional domain for substrate interaction, such as MATH, kelch, Zn finger, and PHR. With the existence of a large number of BTB proteins in human, the Cul3 ubiquitin ligases ubiquitinate a wide range of substrates involving in diverse cellular functions. In this review, we will discuss recent advances on the functions of Cul3 ubiquitin ligases in cancer development, progression, and therapeutic response and the dysregulation of Cul3-mediated ubiquitination events in human malignancies. In particular, we will focus on three Cul3 substrate adaptors, Keap1, KLHL20, and SPOP, with the intent to highlight novel targets in cancer therapy.